Lipopolysaccharide affects metabolic processes and energy homeostasis in the corpus luteum - Mierzejewski, Karol; Stryiński, Robert; Bogacka, Iwona; Golubska, Monika; Carrera, Mónica; Kurzynska, Aleksandra (Frontiers in Molecular Biosciences, 2025)
IntroductionChronic inflammation caused by Escherichia coli infections has a significant negative impact on the reproductive system and impairs fertility. The corpus luteum (CL) plays a central role not only in regulating the ovary cycle, but also in implantation of the embryo and maintenance of early pregnancy through the secretion of progesterone. Understanding the intricate interplay between inflammatory processes and reproductive organ’s function is crucial for the development of effective therapeutic strategies to alleviate reproductive disorders and improve fertility.MethodsThe aim of this study was to determine the in vitro effects of lipopolysaccharide (LPS) on the proteomic profile of the porcine CL in the mid-luteal phase of the estrous cycle using LC-MS/MS analysis. The CL slices were incubated in the presence of LPS for 24 h.ResultsWe identified 12 differentially regulated proteins after treatment with LPS (7 of them were upregulated, while 5 were downregulated). The analysis showed that these proteins are involved in processes such as glucose metabolism, the tricarboxylic acid cycle (TCA), detoxification processes as well as steroid biosynthesis in the CL. Moreover, we demonstrated that LPS decreases glucose levels and increases progesterone levels in the CL.ConclusionThese findings suggest that LPS modulates key metabolic pathways in the CL, potentially impacting its functional activity.